A taxonomic revision of the Afrotropical weevil genus Araxus Marshall (Curculionidae, Brachycerinae, Tanysphyrini) with the description of two new species - Caldara, Roberto; Tedeschi, Michele; Fogato, Valter (Zootaxa, 2026)
The Afrotropical weevil genus Araxus Marshall, 1955 is herein revised for the first time. Based on adult morphological characters, six species are recognized as valid, two of which are new to science: Araxus crassirostris Caldara, Tedeschi & Fogato sp. nov. and A. parallelipennis Caldara, Tedeschi & Fogato sp. nov., both from Central Africa. Lectotypes are designated for Bagous hovanus Hustache, 1920, B. myrmidon Hustache, 1920, and B. ovalipennis Hustache, 1939. Araxus varius Marshall, 1955 is proposed as syn. nov. of Araxus ovalipennis (Hustache, 1939). Male and female genitalia have been examined and illustrated for the first time. The six species are very similar to and separable from each other by a few subtle features in the habitus, the shape of the tibiae, the shape of the rostrum with or without “false” scrobes, and the shape of male and female genitalia. On the basis of morphological characters, the genus is confirmed to belong to the tribe Tanysphyrini, which is currently included, although doubtfully, in the subfamily Brachycerinae (Curculionidae). Characters distinguishing Araxus from the only other Tanysphyrini genus in the Afrotropical region, Afroryzophilus Lyal, 1990, are presented.